Modelling company generic production capabilities in process industries: A configuration approach. Issue 2 (6th February 2017) - Lager, Thomas; Samuelsson, Peter; Storm, Per
Abstract : Purpose: In the process industries, it is essential to have a well-articulated manufacturing strategy within companies. However, to facilitate manufacturing strategy development, it is important to start with a good characterisation of the material transformation system and company production capabilities. The paper aims to discuss these issues. Design/methodology/approach: A grounded theory approach, with inspiration from configuration modelling, attempted to characterize the material transformation system as a set of variables. The variable development was based on a literature review and the knowledge base of five industry experts. Two exploratory mini-case studies were carried out, primarily to illustrate the use of the model, but additionally to test its industrial usability. Findings: A set of 31 variables was developed, and related measures and scales were tentatively defined. Two mini-cases supported the usability of the model. The model, focussing on company generic process capabilities, is a conceptual taxonomy and the study's theoretical contribution. Research limitations/implications: The lucidity of the definitions and scales for the variables are open to further refinement, and the limited discussions of variable relationships in this study are addressed in an agenda for further research. Practical implications: The model can be deployed as a facilitative instrument in the analysis of company material transformation systems and may serve as a platform in further discussions on companies' strategy development. Originality/value: The model is a new instrument for analysing company generic process capabilities and an effort to build new theory rather than to test an existing one.